Profil Program Penyuluh Dalam Usaha Budidaya Ikan Di Desa Muara Aloh Kecamatan Muara Muntai Kabupaten Kutai Kartanegara - wira anugrah; Muhammad Syafril; Wahyu Fahrizal (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
Wira Anugrah Ramadhani, 2021. Profile of Extension Program on Fish Cultivation Business in Muara Aloh Village, Muara Muntai District, Kutai Kartanegara Regency (Advised by Muhammad Syafril and Wahyu Fahrizal).Current research was performed to know the profile of the extension program of fish cultivation business in Muara Aloh Village, Muara Muntai District, Kutai Kartanegara Regency. In this study, the sampling was done using purposive sampling, in which 15 cultivators and 1 extensive worker were selected. Furthermore, the data obtained were further analyzed using descriptive qualitative.Results obtain further show that fishery extension program in Muara AlohVillage includes the aspects of fish cultivator accompaniment, division of facilities and infrastructures, monitoring, as well as evaluation of fish cultivation activities. In the case of fishery extension activities, the method applied by the extensive worker is individual and mass approach. The individual approach was conducted through phone, while the mass approach was conducted through public meeting method. Furthermore, media utilized during the fishery extension activities are printed media, visual media, audio-visual media, and audio media. The printed media are in the forms of brochure and leaflet, the visual media is in the forms of white/black board, the audio-visual is in the forms of slide, and audio media is in the forms of phone. The target of this extension activity is the cultivator, village public figure, and surrounding communities.Keywords: Program Profile, Extension Worker, Fish Cultivator, Muara Aloh